Individualism in Mobile Games; A Semiotic Analysis - H. Aakbari; A. Majdi; M Heydari (Taḥqīqāt-i Farhangī-i Īrān)
Seeking to expand communication technologies, new diversified ‎architecture of the process of ‎transferring meaning is evolving ‎media in the world. One of these methods, conveying the fabric ‎in ‎virtual games. Virtual games as a text, concepts to transmit ‎users. One of the implications of the media ‎in the field of work ‎on it has been less, individualism. The notions that in terms of ‎sociological ‎significance is also due to sign method cognitive ‎Barrett, mobile phone Games were investigated. Five ‎codes on ‎the basis of the five Barrett, four five codes concept of cultural ‎field as individualism, ‎summing up the findings provided urban ‎space, alone, relying on the individual capabilities, ‎human ‎challenge with human.‎